Esterification of palm fatty acid distillate by using manganese oxide and nickel oxide supported on zirconia for biodiesel production - Al-Jaberi, Salam Hussein Hayder (2017)
Energy demand is now increasing on daily basis. This is due to increase in population and technical know how. Conventional fossil fuel reserves are potentially drying, besides, fossil fuel is associated to many environmental issues such as global warming. Biodiesel is found to be promising alternative fuel to conventional fossil fuel. This is due to its renew ability, non-toxic nature, and biodegradability. However, the current biodiesel production using homogeneous catalyst is no longer economical considering the corrosiveness of liquid catalysts and difficulty in separation after use, hence, cannot be reused. Additionally, biodiesel high cost of production is mainly from cost of feed stock which account for more than 80% of total biodiesel production cost. Biodiesel production cost can be reduced by employing non edible feed stock over heterogeneous solid catalyst. Utilizing heterogeneous catalyst for biodiesel production will enable catalyst reusability, reduction in cost of production and proper disposal of used catalyst. In this research, biodiesel was produced by esterification of palm fatty acid distillate (PFAD) with methanol using heterogeneous manganese-nickel doped on sulfated zirconia catalyst (MnO-NiO-SO42-/ZrO2). Initially, the catalyst was synthesized using simple wet impregnation method in five different concentrations of manganese 5%-25% and nickel (5%-25%) supported on zirconia. After catalyst screening, two out of five showed significant FFA conversion when concentration of manganese was 10%Mn and the concentration of nickel was 15%NiO after doping manganese and nickel on zirconia under the best concentration and then the catalyst activity was improved by increasing the acidity via treatment with chlorosulfonic acid to form 10%Mn-15%NiO-4%SO42-/ ZrO2. The best catalyst was characterized using different characterization techniques in order to study the physic-chemical properties of the catalyst. The optimization of esterification reaction conditions of PFAD using heterogeneous solid catalysts was performed. The TPD-NH3 result of the synthesized solid acid catalyst proved the catalytic activity of the catalyst, having achieved 97.7% FFA conversion due to high strength of acid sites. Moreover, the catalyst was reused for at least 5 cycles before complete deactivation of the catalytic active phase.